Blue skies and boiler rooms : buying and selling securities in Canada, 1870-1940 - Armstrong, Christopher, 1942- (University of Toronto Press, 1997)
Blue Skies and Boiler Rooms describes the evolution of the securities market in Canada, from the onset of trading, through the boom of the 1920s and the depression of the 1930s, to the outbreak of the Second World War. The book documents the problems of fraud, misrepresentation, and manipulation of prices, which plagued the securities industry from the outset and which eventually led to market regulation, first by the stock exchanges and later, after the First World War, by governments.